A new genus and species of the paraneopteran family Archipsyllidae in mid-Cretaceous amber of Myanmar - Liang, Feiyang; Zhang, Weiwei; Liu, Xingyue (Zootaxa, 2016)
Paraneoptera is a group of orders, representing one of the highly diverse clades of winged insects. Paleozoic and Mesozoic fossil paraneopterans include a few primitive species, which are significant for understanding the early evolution of Paraneoptera. Here we report a new genus and species, namely Burmopsylla maculata gen. et sp. nov. from the mid-Cretaceous (ca. 99 Myr) amber of Myanmar. The new genus belongs to the family Archipsyllidae by having hindwing similar to forewing (shape, size and venation), presence of forewing ra-rp, rp-m and cua-cup crossveins, two-branched R, four-branched M, and four-segmented tarsus. The new species represents the second species of Archipsyllidae in Cretaceous Burmese amber.